1998
DOI: 10.1177/030802269806100802
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Stress and Perceived Need for Supervision in Senior Occupational Therapy Staff

Abstract: A survey was carried out to examine the links between self·reported levels of tress in occupational therapists, the perceived needs for professional supervision and future job intentions. A request was posted to a representative sample of 60 occupational therapy manager , who were each asked to give out anonymous questionnaire to five senior occupational therapy taff. Th questionn ire asked for information on grade, length of tim ince qu hfymg, p cialty area, perceived level of stres , extent of atisfaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Previous research has found that social workers (Jones et al, 1991;Farley, 1994;Collings and Murray, 1996) and occupational therapists (Rees and Smith, 1991;Alan and Ledwith, 1998) perceived their job to be very pressured. Social workers experienced slightly more workload stress than occupational therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that social workers (Jones et al, 1991;Farley, 1994;Collings and Murray, 1996) and occupational therapists (Rees and Smith, 1991;Alan and Ledwith, 1998) perceived their job to be very pressured. Social workers experienced slightly more workload stress than occupational therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding burnout, the few studies that have been conducted to date on the topic among therapists working with child trauma victims and occupational social workers have found extensive use of supervision to mitigate that phenomenon (Allan & Ledwith, 1998;Azar, 2000). In contrast, Clarke (2008) revealed that among clinical psychologists who treat private patients, participation in group supervision did not correlate significantly with burnout.…”
Section: Supervision Secondary Traumatization and Burnoutmentioning
confidence: 99%
“…The occupational therapy literature is relatively silent on the subject of supervision and few studies have been carried out examining supervision and occupational therapy. One such study was carried out by Allan and Ledwith (1998) who surveyed 211 occupational therapists (response rate of 70%) to examine the links between self-reported levels of stress in senior occupational therapists, the perceived need for professional supervision and future job intentions. One-third of the staff reported high or very high levels of stress and 19% of respondents said that they intended to have a job outside occupational therapy within five years.…”
Section: Supervisionmentioning
confidence: 99%